Pengaruh E-WOM, Endorser Influencer, dan E-Service Quality Terhadap Keputusan Pembelian Online Pada Live Streaming TikTok Di Kabupaten Boyolali - Charisma Octaviana Saputri; Andri Nurtantiono (ITB AAS Indonesia Surakarta, 2024)
The objective of this research is to examine the effects of E-WOM (electronic word-of-mouth), endorser influencer, and e-service quality variables on the decision-making process for online purchases during live streaming sessions on the TikTok platform. TikTok has gained immense popularity as a social media hub, especially for influencers to engage directly with their audience. The primary data for this research were gathered through the administration of a focused questionnaire survey. To active TikTok users involved in live streaming and making purchasing decisions. Purposive sampling, based on specific criteria, was employed to select 120 respondents. The research combines data collected directly through questionnaires and information obtained from a review of existing literature. The outcomes of the data analysis reveal that the variables of E-WOM, endorser influencer, and e-service quality significantly and positively influence decisions related to online purchases. Keywords : E-WOM, Endorser Influencer,,E-Service Quality, Online Purchases Decisions.